Epidemiology, genetics and treatment of multiple myeloma and precursor diseases - Hemminki, Kari; Försti, Asta; Houlston, Richard; Sud, Amit (International journal of cancer, 2021)
Multiple myeloma (MM) is a hematological malignancy caused by the clonal expansion of plasma cells. The incidence of MM worldwide is increasing with greater than 140 000 people being diagnosed with MM per year. Whereas 5-year survival after a diagnosis of MM has improved from 28% in 1975 to 56% in 2012, the disease remains essentially incurable. In this review, we summarize our current understanding of MM including its epidemiology, genetics and biology. We will also provide an overview of MM management that has led to improvements in survival, including recent changes to diagnosis and therapies. Areas of unmet need include the management of patients with high-risk MM, those with reduced performance status and those refractory to standard therapies. Ongoing research into the biology and early detection of MM as well as the development of novel therapies, such as immunotherapies, has the potential to influence MM practice in the future.
Keywords: nádorové biomarkery; represorové proteiny; Biomarkers, Tumor; Humans; Histone Demethylases; Genetic Predisposition to Disease; genetická predispozice k nemoci; Mutation; míra přežití; Cyclin D1; Repressor Proteins; transkripční elongační faktory; Multiple Myeloma; Risk Factors; Survival Rate; histondemethylasy; plazmatické buňky; Plasma Cells; rizikové faktory; exozom; imunoterapie; Exosome Multienzyme Ribonuclease Complex; Transcriptional Elongation Factors; cyklin D1; lidé; mutace; mnohočetný myelom; Immunotherapy